Gereja yang Menua: Sebuah Konstruksi Eklesiologi Berdasarkan Teologi Penuaan - Eunike Alvonciani (Veritas : Jurnal Teologi dan Pelayanan, 2022)
This article proposes the concept of an aging church as an ecclesiological construction that is based on the theology of aging. It begins with a concern about the tendency of the church to measure its “success” through its productivity, hence forgetting to reflect upon its dependence on God. Using literature analysis and constructive methods, this article combines the aging theology from Autumn Ridenour, Kevin Barnard, and several other theologians with the ecclesiology of John Zizioulas and Michael Jinkins. Analysis of aging theology and ecclesiology are used as the basis for constructing the “aging church”. The thesis of this article is that the church that is aware of its aging also realizes its relational identity in God which can be lived through appreciation of its passive agency in balance with its active agency, as it should be in an aging individual person. The aging church does not specifically refer to the age of the church, but to the relationship with God which invites the church to embrace the past through repentance, realize its relational identity in the present, and renew itself with an eschatological orientation toward the future. Finally, eschatological hope in the passive role of the church of this kind helps the church to see its movements during a pandemic, even a post-pandemic stage so that they are not trapped in non-essential productivity.